(3GdETQGa Ydi GdCTQGas
(3ChdgG (B:s
(3GdMeO ddg GdPi aVd gPg GdGeI Ydi SGFQ GdGee bGd HYV GdYdeGA Gf Gddg LYd PQjI GdfHi Udi Gddg Ydjg hSde eSGhjf dg ai GTjGA cKjQg YO GdaNQ GdQGRi efgG NeSI GTjGA s
(3BNQgG (B:s
(3GdeQJLi Gf fhGajg HWjHJce haGJg ajhGai GdYah ef cQe Ke GdUdGI Ydjce SQ eOkG GHOkG LYdJg dc ai HOGi heNJJe JeJ hgPG BNQ eG HYK Gddg HLeYg s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJGQjNs